2016
DOI: 10.1155/2016/5082678
|View full text |Cite
|
Sign up to set email alerts
|

Modelling of Sudan’s Energy Supply, Transformation, and Demand

Abstract: The study aimed to develop energy flow diagram (Sankey diagram) of Sudan for the base year 2014. The developed Sankey diagram is the first of its kind in Sudan. The available energy balance for the base year 2012 is a simple line draw and did not count the energy supply by private and mixed sectors such as sugar and oil industries and marine and civil aviation. The private and mixed sectors account for about 7% of the national grid electric power. Four energy modules are developed: resources, transformation, d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 2 publications
0
7
0
Order By: Relevance
“…As of September 2019, the Government of South Sudan had announced its intentions to tap the immense renewable energy sources of the country by launching a plan aimed at defining the country's renewable energy course of development, and there are plans to secure US$ 990,000 for a renewable energy program [53]. It is anticipated that the development of solar power would decouple economic growth from the geopolitics of oil and gas [54]. Nonetheless, the literature indicates that photovoltaics are the main technological means for tapping solar power in the country, with a total installed capacity of 2 MW.…”
Section: South Sudanmentioning
confidence: 99%
“…As of September 2019, the Government of South Sudan had announced its intentions to tap the immense renewable energy sources of the country by launching a plan aimed at defining the country's renewable energy course of development, and there are plans to secure US$ 990,000 for a renewable energy program [53]. It is anticipated that the development of solar power would decouple economic growth from the geopolitics of oil and gas [54]. Nonetheless, the literature indicates that photovoltaics are the main technological means for tapping solar power in the country, with a total installed capacity of 2 MW.…”
Section: South Sudanmentioning
confidence: 99%
“…The available biomass for energy also excludes that goes as animal feed, construction, and other industries. The available biomass for energy is about 11 Mt/year, with an energy content of 154 PJ/year (154 × 10 15 J), equivalent to 3.68 Mtoe (1 TJ = 2:388 × 10 −5 Mtoe) [1][2][3][4]. The potential electric generation from biomass is about 1 GW.…”
Section: Introductionmentioning
confidence: 99%
“…Sudan is very rich in solar radiation and has long sunshine hours all over the country, Osman [2] and Rabah et al [3]. It is one of the top solar energy regions of the world.…”
Section: Introductionmentioning
confidence: 99%
“…It has an average sunshine duration ranging from 8.5 to 11 hours per day, solar radiation from 20 to 25 MJ m -2 day -1 on the horizontal surface, and an annual daily mean global radiation ranges from 3.05 -7.62 kWm -2 day -1 , Omer [4]. Nevertheless, according to the study by Rabah et al [3] addressing Sudan's energy supply, transformation and demand; it was found that the Sudan's energy consists of oil (39%), biomass (56%), and hydroelectricity (5%). The study showed that solar energy, mainly photovoltaic, contribution is very little.…”
Section: Introductionmentioning
confidence: 99%